The effect of optimum, indication-specific imaging fields on the radiation exposure from CBCT examinations of impacted maxillary canines and mandibular third molars - Ilo, Anne-Mari (Taylor & Francis, 2025)
Objective Indication-specific optimum field-of-views (FOVs) have been assessed for CBCT scans of impacted maxillary canines and mandibular third molars, as 40∅ × 35 mm and 35∅ × 35 mm, respectively. The objective was to investigate possible changes in absorbed organs and effective doses, for these two imaging indications, performing CBCT examinations with optimum FOV sizes instead of commonly used FOVs. Additionally, radiation exposure-induced cancer risk was calculated for both imaging indications with optimum FOVs.
Methods An adult female head phantom (ATOM 702-D, CIRS, Norfolk, VA, USA) was scanned using Planmeca Viso G7 CBCT-device (Planmeca, Helsinki, Finland). Scanning factors, different FOV sizes, dose-area product (DAP) values and anatomical FOV locations were used for Monte Carlo PCXMC-simulation and ImpactMC software. In the PCXMC- simulation, 10-year-old child and 30-year-old adult phantoms were used to estimating effective and absorbed organ doses.
Results The effective dose varied from 58 µSv to 284 µSv for impacted maxillary canines, and from 38 µSv to 122 µSv for mandibular third molars, the lowest dose value for each corresponding to optimum FOV. Effective dose reduction between the optimum FOV and the smallest common FOV of 50∅ × 50 mm, maintaining other scanning factors constant, was 33% for impacted maxillary canines, and 45% for mandibular third molars. At all examinations, the highest absorbed organ doses were in salivary glands or in oral mucosa.
Conclusions Optimum FOVs, 40∅ × 35 mm for impacted maxillary canine and 35∅ × 35 mm for mandibular third molar, could decrease effective doses received by young patients, and improve radiation safety in these common CBCT imaging procedures.